Triangular osteosynthesis and lumbopelvic fixation as a valid surgical treatment in posterior pelvic ring lesions: a systematic review - Rovere, Giuseppe; De Mauro, Domenico; Smakaj, Amarildo; Sassara, Giulia; De Vitis, Rocco; Farsetti, Pasquale; Camarda, Lawrence; Maccauro, Giulio; Liuzza, Francesco (Frontiers in Surgery, 2024)
Unstable fractures of the sacrum often occur in patients with pelvic fractures and represent a real challenge for the orthopedic surgeon. Triangular osteosynthesis (TOS) and lumbopelvic fixation (LP) may represent a valid management option for the treatment of this condition. We present a systematic literature review about lumbopelvic fixation and triangular fixation as treatment option for unstable sacral fractures, to assess clinical and radiological outcomes after surgery and to evaluate appropriate indications and impact on the natural history of sacral fractures.The review is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines . 50 articles out of 108 titles, were considered eligible for the fulltext analysis. Finally, 16 studies that met inclusion criteria were included in this reviewOverall, 212 patients (87 males, 58 females) with sacral fractures treated with TOS triangular fixation or LP lumbopelvic fixation were collected. The mean age was 37.6 years. Mean follow-up reported in all studies was 24.14 months.The results presented by the different authors, highlight the effectiveness of TOS triangular fixation and LP lumbopelvic fixation for the treatment of unstable sacral fractures associated with other pelvic fractures, in terms of function, stability, cost-effectiveness, and quality of life postoperatively.